STUDY THE EFFECT OF REINFORCING FIBER TYPES ON CREEP BEHAVIOR OF PROSTHETIC SOCKET (THE IRAQI JOURNAL FOR MECHANICAL AND MATERIALS ENGINEERING, 2025)
Due to the difficult conditions in Iraq and the increasing frequency of terrorist attacks, the number of amputees has skyrocketed. However, trans-tibial amputations account for about 80% of all amputations. The creep behavior of composites was investigated using tensile creep testing. In this investigation, fifteen laminated composites were used. The polyester polymer was used as the matrix and strengthened with fibers, including jute, glass, hemp, carbon, and person, which were created by the vacuum molding process. Socket materials were evaluated for their mechanical properties to select a laminated composite that must support loads for prolonged periods. According to the data, the best-laminated samples contained two layers of carbon fiber and three layers of natural fiber. This indicates that the hemp-carbon hybrid with a 0.00031(%/hr.) creep rate is more resistant to creep than natural fiber alone or other hybrids. As the total of fiber layers rises, the creep rate lowers. This investigation concluded that the mechanical assets were affected by the kind and quantity of supporting layers. These results highlight the natural fiber laminate's potential for orthopedic applications with improved biocompatibility.